Inhibitors of histone deacetylase 6 based on a novel 3-hydroxy-isoxazole zinc binding group - Pasquale Linciano; Luca Pinzi; Silvia Belluti; Ugo Chianese; Rosaria Benedetti; Davide Moi; Lucia Altucci; Silvia Franchini; Carol Imbriano; Claudia Sorbi; Giulio Rastelli (Taylor & Francis Group, 2021)
Histone deacetylase 6 (HDAC6) is an established drug target for cancer treatment. Inhibitors of HDAC6 based on a hydroxamic acid zinc binding group (ZBG) are often associated with undesirable side effects. Herein, we describe the identification of HDAC6 inhibitors based on a completely new 3-hydroxy-isoxazole ZBG. A series of derivatives decorated with different aromatic or heteroaromatic linkers, and various cap groups were synthesised and biologically tested. In vitro tests demonstrated that some compounds are able to inhibit HDAC6 with good potency, the best candidate reaching an IC50 of 700 nM. Such good potency obtained with a completely new ZBG make these compounds particularly attractive. The effect of the most active inhibitors on the acetylation levels of histone H3 and α- tubulin and their anti-proliferative activity of DU145 cells were also investigated. Docking studies were performed to evaluate the binding mode of these new derivatives and discuss structure-activity relationships.